ADDIE method for implementation of virtual reality in online course using model project-based learning - Herri Akhmad Bukhori; S Sunarti; Tiksno Widyatmoko; Hie Ling Ting (University of Muhammadiyah Malang, 2022)
This research aims to implement virtual reality (VR) in online learning for the Chinese language of learning. Model learning in this research is project-based learning to support media in VR. The development of VR in online learning used the ADDIE method because this research developed a media and for using it, students have model learning as project-based learning. The target of this research is the effectiveness of using VR in online learning to improve the cognition of students. In this research, VR was tested by 20 students to get data on students’ cognition. The result of this research, VR had effective around 78% compared to without using VR